Exploring Senior High School English Teachers’ Content Knowledge in West Pasaman Regency - Retno Astagina; Aryuliva Adnan (Journal of English Language Teaching, 2022)
This study was conducted to determine the content knowledge of senior high school English teachers in West Pasaman Regency, West Sumatera. The content knowledge is about the teachers' knowledge of the material and how the teacher developed the material. The study was descriptive-qualitative and employed two methods, a document and a questionnaire, to gather data. Eight teachers from various schools were chosen to participate in this study using a purposive sampling technique. The findings of this study indicate that teachers have a good mastery of the subject matter. However, none of the teachers developed or adapted the material. Therefore, it is still necessary to strengthen teacher content knowledge so that they may build materials designed to meet their students' requirements.